Hasil Belajar Siswa Pada Tari Persembahan Bengkulu Di SDN 68 Kota Bengkulu - Dwi Anggraini; Neza Agusdianita; Agustini Novikasari (JURIDIKDAS, 2018)
This study aims to determine the effectiveness of learning and skills Culture Art Class III SD Negeri 68 of Bengkulu and how student learning outcomes in the cognitive, affective and psychomotor aspects of the third grade students. This type of research is descriptive quantitative techniques percentage. The study population was around the third grade students of SD Negeri 68 Bengkulu City. Samples were students of class III B SD Negeri 68 Bengkulu City. Data were analyzed using a multiplechoice test sheet, and the observation sheet. The results showed that the cognitive aspect there are 17 students from 24 students who are in the category capable with the percentage 70.83%, a category not able to have 7 students with a percentage of 29.16%. On the affective value of students in a category is able to have 16 students with a percentage of 66.67%, the category is not able to have 8 students with a percentage of 33.33%. On the psychomotor aspects of students in a category is able to have 15 students with a percentage of 62.5% and the categories are not able to have 9 students with a percentage of 37.5%. It was concluded that student learning outcomes in these three aspects vary. Students who get good cognitive value, not necessarily getting a good value also on affective and psychomotor.